HUBUNGAN BIMBINGAN KONSELING DAN PENDIDIKAN AGAMA ISLAM DALAM PENANAMAN KARAKTER YANG BAIK PADA DIRI SISWA/I DI SMA ETHIKA PALEMBANG - Marlia, Ani; Atika Sary, Febriany; Sukandi, Ricko; Dimas Purnawan, Muhammad; Ridhayanti, Irma; Sakinah, Annisa; Vitriani, Novi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
Guidance and counseling and islamic religious education are good collaborations in forming character in students. In this article the author uses a qualitative method where the author seeks information by distributing a questionnaire and interviewing several people. Because of the problem, namely the absence of counseling guidance in some schools and teachers ignorance about the relationship between counseling guidance and Islamic religious education, the author wrote this article so that readers can take a lesson from the relationship between counseling guidance and Islamic religious education carried out at Ethika High School. The conclusion in this article is that currently quite a few Islamic religious education teachers and guidance counseling teachers understand that they have a relationship with a responsibility to shape the charater of a student. Islamic religious education is the best complement or collaboration in forming student character. Islamic religious education itself is an effort made by educators towards students in forming and instilling faith, devotion and creating a good personality in each student in the form of teaching and learning, training.